Biocontrol assessment of Trichoderma species on tomato crops infested by Curvularia Spicifera: toward sustainable farming systems - Hajji-Hedfi, Lobna; Rhouma, Abdelhak; Wannassi, Takwa; Utkina, Aleksandra O.; Rebouh, Nazih Y. (Frontiers in Sustainable Food Systems, 2025)
This study provides the first comprehensive evaluation of the efficacy of three Trichoderma species (Trichoderma longibrachiatum, Trichoderma harzianum, and Trichoderma asperellum) in controlling Curvularia spicifera on tomato plants under both in vitro and in vivo conditions. Laboratory-based experiments assays, including direct and indirect confrontation, application of culture filtrates, and inhibition of spore germination, demonstrated significant antagonistic activity by the Trichoderma species. These treatments markedly reduced the mycelial growth (<2.63 cm), mycelial growth rate (<1.28 mm/h), and spore germination (<0.40) of C. spicifera, with T. longibrachiatum exhibiting the strongest antagonistic effect. The efficacy of three Trichoderma spp. and salicylic acid was evaluated under greenhouse conditions. Greenhouse trials further confirmed that T. longibrachiatum (2.83) significantly reduced disease severity compared to the control inoculated with C. spicifera (5.50) at 90 days post-inoculation (dpi). Biochemical analysis revealed an increase in enzyme activity and total protein content in the leaves and roots of Trichoderma-treated plants, with values of 10.09 and 10.44 mg g−1, respectively. These changes reflect an induced defense response. Specifically, T. longibrachiatum consistently induced higher activities of catalase (74.58 and 73.1 μmol H2O2 mg protein−1, respectively), peroxidase (5.35 and 54.91 μmol mg−1 min−1, respectively), ascorbate peroxidase (54.91 and 60.29 μmol mg−1 min−1, respectively), and polyphenol oxidase (14.07 and 9.37 units mg−1 min−1, respectively) in tomato leaves and roots at 90 dpi. Furthermore, T. longibrachiatum significantly enhanced chlorophyll content and other agronomic traits, including root and shoot biomass, fruit yield, and overall plant growth. These findings suggest that T. longibrachiatum is a promising biocontrol agent against C. spicifera in tomato plants, promoting both plant growth and the activation of defense mechanisms.